KELEMBAGAAN PENGELOLA MINYAK DAN GAS BUMI PASCA PUTUSAN MAHKAMAH KONSTITUSI (STUDI PUTUSAN MAHKAMAH KONSTITUSI NOMOR 36/PUU-X/2012) - Ganesha Patria Wicaksono (Yuridika, 2015)
BP Migas the kind of reform agenda from institutional manager oil and gas which is the part of Undang-Undang Nomor 22 Tahun 2001. BP Migas is institusional manager of oil and gas that formed to become the government representation as mining rights to controlling and supervising exploration and exploitation oil and gas that formerly held by pertamina. Politiekrecht establishment BP Migas is to avoiding conflict of interest if the regulation function and business has been place in the same institutional like the old Pertamina, so doing the separation institutional which do the function of regulation and business. The existancy of BP Migas impact to the mining rights which is the part of the authority of state control become obscuur ,because the fifth function that constructed by Constitutional Court by doing interpretation to  section 33 act (2) dan (3) UUD NRI Tahun 1945 can’t through all and gradual. Through Constitutional Court decision No 36/PUU-X/2012 all the section which have related with BP Migas are unconstitutional. BP Migas should be dissolved and government from the regulation function should control the new institutionals function and authority. With the dissolution of BP Migas the government would establish similar function and authority institutional which named SKK Migas .With the present SKK Migas, so all the mining rights problems become interested to be re-examined.